Peranan Perempuan Nelayan Kota Padang dalam Membantu Ekonomi Keluarga - Najmi Najmi; Azmi Fitrisia (Diakronika, 2019)
This research explains the role of women fishermen (fishermen's wife) in assisting family economic needs. Fishermen who have economies below average are considered unable to meet their daily needs. Fishermen are jobs that bear considerable risk. In addition to the many shipping supplies and fishing gear they need, the risk of weather also greatly affects. For example if a storm hit the beach, then they automatically cannot get down to the sea and it is difficult to catch fish. Here the role of women is needed. Automated women cannot always rely on their husband to meet family needs. Here comes the role of two women who are certainly very helpful to the fisherman especially in the economic field. Various jobs such as sewing, trading such as opening a shop and other work. Here also will be found various problems such as women ignore their health and whether there is a role of government in paying attention to this, especially the local government. This research uses field observation method through interview and some data needed such as document as additional material. Interviews were conducted with fishermen and women fishermen at the study sites. Then also use the method of history in general, where data from the results of the interview will also be criticized and analyzed.